2017
DOI: 10.1021/acs.joc.7b00643
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Cascade Synthesis of Quinazolin-4(3H)-ones via Nickel-Catalyzed Dehydrogenative Coupling of o-Aminobenzamides with Alcohols

Abstract: In this paper, we report a general, efficient, and environmentally benign method for the one-pot cascade synthesis of quinazolin-4(3H)-ones via acceptorless dehydrogenative coupling of o-aminobenzamide with alcohols catalyzed by a simple Ni(II) catalyst, [Ni(MeTAA)], featuring a tetraaza macrocyclic ligand (tetramethyltetraaza[14]annulene (MeTAA)). A wide variety of substituted quinazolin-4(3H)-ones were synthesized in high yields starting from readily available benzyl alcohols and o-aminobenzamides. Several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 84 publications
(35 reference statements)
1
54
0
Order By: Relevance
“…The chemistry of iodine(V) reagents has been well documented in a number of reviews [1820]. In continuation of our research focus on the development of synthetic methods using iodine-based reagents [2126], we here report a method for the synthesis of quinazolin-4(3 H )-ones [2728] (Fig. 1) from 2-aminobenzamide and aldehydes in the presence of o -iodoxybenzoic acid (IBX) [29].…”
Section: Resultsmentioning
confidence: 99%
“…The chemistry of iodine(V) reagents has been well documented in a number of reviews [1820]. In continuation of our research focus on the development of synthetic methods using iodine-based reagents [2126], we here report a method for the synthesis of quinazolin-4(3 H )-ones [2728] (Fig. 1) from 2-aminobenzamide and aldehydes in the presence of o -iodoxybenzoic acid (IBX) [29].…”
Section: Resultsmentioning
confidence: 99%
“…The dehydrogenative pathway possibly proceeds through the initial formation of alkoxy nickel species which undergo β‐elimination to form reactive aldehyde and nickel hydride species. Then sequential coupling with o ‐aminobenzamides and oxidization with the released nickel hydride species deliver quinazolin(3 H )‐4‐ones (Scheme ) …”
Section: Nickel‐catalyzed Dehydrogenative Bond Formationsmentioning
confidence: 99%
“…The catalysts 1 a and 1 b represent two tetraaza macrocyclic nickel(II)‐complexes, whereas catalysts 2 a and 2 b are two diamine‐based nickel(II)‐complexes. During our recent works, we observed that the nickel catalysts 1 a and 1 b involve exclusively nickel‐centered redox events during catalysis and the dehydrogenation of alcohols proceeds via two‐electron hydride transfer process involving energetically demanding nickel centered redox states at high temperature . On the other hand, in presence of 2 a and 2 b dehydrogenation of alcohols proceed via one‐electron hydrogen atom transfer (HAT) process (avoiding the unfavourable nickel centered two‐electron process) where the coordinated redox‐active ligand abstract a α‐hydrogen atom of the alcohol to form an O‐coordinated ketyl radical intermediate which undergo rapid one‐electron oxidation to yield the respective carbonyls .…”
Section: Introductionmentioning
confidence: 99%